2006
DOI: 10.1073/pnas.0609225103
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spines linearize the summation of excitatory potentials

Abstract: In mammalian cortex, most excitatory inputs occur on dendritic spines, avoiding dendritic shafts. Although spines biochemically isolate inputs, nonspiny neurons can also implement biochemical compartmentalization; so, it is possible that spines have an additional function. We have recently shown that the spine neck can filter membrane potentials going into and out of the spine. To investigate the potential function of this electrical filtering, we used two-photon uncaging of glutamate and compared the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 39 publications
3
113
1
Order By: Relevance
“…These experiments also suggest that additional dendritic depolarization, e.g., by coincident backpropagating APs or by simultaneously active neighboring synapses, would strongly boost spine depolarization. The previously reported linear summation of uncaging-evoked potentials on spines (Araya et al, 2006) can be explained by such an active amplification process (supplemental Fig. 3, available at www.jneurosci.org as supplemental material).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…These experiments also suggest that additional dendritic depolarization, e.g., by coincident backpropagating APs or by simultaneously active neighboring synapses, would strongly boost spine depolarization. The previously reported linear summation of uncaging-evoked potentials on spines (Araya et al, 2006) can be explained by such an active amplification process (supplemental Fig. 3, available at www.jneurosci.org as supplemental material).…”
Section: Resultsmentioning
confidence: 80%
“…Third, for the activation of multiple inputs on the same dendrite, different modes of integration have been reported: sublinear, linear, and supralinear (Polsky et al, 2004;Araya et al, 2006;Gasparini and Magee, 2006;Sjöström et al, 2008). Integration has been shown to depend on the activation of voltage-gated channels and NMDA receptors and is therefore an active process Carter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling has demonstrated that the unique structure and molecular composition of dendritic spines contribute to their ability to act as discrete isolated computational units (Pongracz 1985;Rall et al 1967), filter electrical noise Yuste 2002, 2004), and aid in linear summation (Araya et al 2006;Lev-Tov et al 1983;Yuste and Urban 2004). Computational studies have also been used extensively to complement recent experimental data (Matsuzaki 2007;Matsuzaki et al 2004;Segev and Rall 1998).…”
Section: R E S U L T Smentioning
confidence: 99%
“…Voltage sensitive membrane specific markers have permitted for single site time dependent optical recordings of membrane potential activity [32][33][34][35][36][37]. This enabled the team of Yuste and Eisenthal to measure the length of the dendritic spine necks in living neurons and to determine that dendritic spines linearize the summation of excitatory potentials [38]. In another promising approach, SHG active surface modifiable non-centrosymmetric nanodoublers [39] have been introduced as a practical alternative to fluorescent molecules and quantum dots, to track processes through in-vitro (cell) imaging [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%